Label‐Free Biomedical Imaging of Lipids by Stimulated Raman Scattering Microscopy. Issue 1 (5th January 2015) - Ramachandran, Prasanna V.; Mutlu, Ayse Sena; Wang, Meng C.
Abstract: Advances in modern optical microscopy have provided unparalleled tools to study intracellular structure and function, yet visualizing lipid molecules within a cell remains challenging. Stimulated Raman Scattering (SRS) microscopy is a recently developed imaging modality that addresses this challenge. By selectively imaging the vibration of chemical moieties enriched in lipids, this technique allows for rapid imaging of lipid molecules in vivo without the need for perturbative extrinsic labels. SRS microscopy has been effectively employed in the study of fat metabolism, helping uncover novel regulators of lipid storage. This unit provides a brief introduction to the principle of SRS microscopy, and describes methods for its use in imaging lipids in cells, tissues, and whole organisms. © 2015 by John Wiley & Sons, Inc.